Application of pavement condition index (PCI) assessment method for rural road maintenance in Kuching-Samarahan area - Shawn, Mckenzie (Universiti Malaysia Sarawak (UNIMAS), 2012)
Road is very important infrastructure as mean of access for the community that lives in rural area. Rual roads need to be regularly maintained to ensure achieving serviceable lifespan and continuously to be in good, optimum condition. The aim of this study is to conduct the Pavement Condition Index (PCI) assessment method to selected rual roads within Kuching-Samaahan area. Pavement defects can be assessed using Visual Assessment Method or Mechanized Method. Visual inspections are normally used to record all conspicious defects of pavement, shoulders, ditches,culverts, slopes and road furniture. Mechanized method is more repeatable, reproducibleand generally, can be collected more efficiently.